2021
DOI: 10.1021/acs.joc.1c01017
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electrosynthesis of Anthranilic Acid Derivatives via a C–C Bond Cleavage of Isatins

Abstract: A facile and direct electrocatalytic C–C bond cleavage/functionalization reaction of isatins was developed. With isatins as the amino-attached C1 sources, a variety of aminobenzoates, and aminobenzamides were synthesized in moderate to good yields under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…2.5.2 Synthesis of anthranilic acid derivatives. Wang's group (in 2021) synthesized 21 anthranilic acid derivatives via the oxidative ring-opening of isatins under electrochemical conditions in an undivided cell using Pt as electrodes, tetrabutylammonium perchlorate (n-Bu 4 NClO 4 ) as electrolyte and MeOH/CH 3 CN as mixed solvent (Scheme 14). The authors have reported that no product was observed without electricity and a constant current of 15 mA was necessary for getting a maximum product yield.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…2.5.2 Synthesis of anthranilic acid derivatives. Wang's group (in 2021) synthesized 21 anthranilic acid derivatives via the oxidative ring-opening of isatins under electrochemical conditions in an undivided cell using Pt as electrodes, tetrabutylammonium perchlorate (n-Bu 4 NClO 4 ) as electrolyte and MeOH/CH 3 CN as mixed solvent (Scheme 14). The authors have reported that no product was observed without electricity and a constant current of 15 mA was necessary for getting a maximum product yield.…”
Section: Reviewmentioning
confidence: 99%
“…Next, MeO − could react with isatin to give intermediate I26 which should be converted to intermediate I27 in the presence In 2023, Weng and Gao's group 22 reported electrochemical chemo-selective transformations of isatins to anthranilic acid derivatives (Scheme 16). They reacted isatins (1a) with tyrosinecontaining biomolecules (20) to obtain the desired modified tyrosine products (21) in the presence of n-Bu 4 NF•3H 2 O as electrolyte and MeCN as a solvent, with an electrochemical setup of a platinum plate as the anode and a lead plate as the cathode (Scheme 16). The product was formed due to an electrochemical C-C bond cleavage of the isatin starting material.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…[29][30][31] Historically, various methodologies have been employed for tyrosine modification, encompassing Mannich-type reactions, π-allyl Pd complexes, and Ru photocatalysts. [32][33][34][35][36][37] However, the challenge of functionalizing tyrosine with useful moieties in the absence of additives remains formidable. Consequently, the development of a clean, mild, and metal-free strategy for achieving site-selective tyrosine modification holds great allure for the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the revival of electrochemical organic synthesis has provided a new opportunity and alternative for greener and more sustainable synthetic procedures . Recently, some remarkable progress in electrochemically enabled Hofmann rearrangement reactions has made a deep impression on the community of synthetic chemistry, making Hofmann rearrangement reactions an environmentally friendly strategy without using traditional chemical oxidants (Scheme c). - In 2018, Xu and Zhang reported the preparation of carbamates by NaBr-mediated electrochemical Hofmann rearrangement of benzamides and aliphatic amides . In 2021, an adjustable methodology for the synthesis of anthranilic acids via the electrochemical Hofmann ring-opening of isatins was demonstrated by the Wang group .…”
Section: Introductionmentioning
confidence: 99%
“…10 In 2021, an adjustable methodology for the synthesis of anthranilic acids via the electrochemical Hofmann ring-opening of isatins was demon-strated by the Wang group. 11 Notably, Guo and co-workers developed the construction of anthranilic acid derivatives through the electrochemical oxidative ring-opening reactions of indoles with alcohols. 12 Phthalimide and its analogues are widely used in organic synthesis as versatile building blocks, 13 as well as in the field of pharmaceutical chemistry due to their rich biological activities.…”
Section: ■ Introductionmentioning
confidence: 99%